2019
DOI: 10.1093/cid/ciz076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics, Pharmacodynamics, Safety and Efficacy of Liposomal Amphotericin B

Abstract: Since its introduction in the 1990s, liposomal amphotericin B (LAmB) continues to be an important agent for the treatment of invasive fungal diseases caused by a wide variety of yeasts and molds. This liposomal formulation was developed to improve the tolerability of intravenous amphotericin B, while optimizing its clinical efficacy. Since then, numerous clinical studies have been conducted, collecting a comprehensive body of evidence on its efficacy, safety, and tolerability in the preclinical and clinical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 119 publications
0
68
0
Order By: Relevance
“…Let us consider amphotericin B, which is characterized by a broad spectrum of antifungal efficacy and is an essential compound in the antifungal armamentarium (Lanza et al 2019). However, the clinical utility of amphotericin B has been restricted by its dose-limiting and potentially fatal nephrotoxicity (Groll et al 2019;Lanza et al 2019). Consequently, dermatophytoses are a real problem especially in children, elderly patients and pregnant women, in whom an adverse effect is unacceptable due to the need for a special cautious approach in these groups of people (Kaul et al 2017).…”
Section: Limited Cellular Targets and Side Effects Of Available Antifmentioning
confidence: 99%
“…Let us consider amphotericin B, which is characterized by a broad spectrum of antifungal efficacy and is an essential compound in the antifungal armamentarium (Lanza et al 2019). However, the clinical utility of amphotericin B has been restricted by its dose-limiting and potentially fatal nephrotoxicity (Groll et al 2019;Lanza et al 2019). Consequently, dermatophytoses are a real problem especially in children, elderly patients and pregnant women, in whom an adverse effect is unacceptable due to the need for a special cautious approach in these groups of people (Kaul et al 2017).…”
Section: Limited Cellular Targets and Side Effects Of Available Antifmentioning
confidence: 99%
“…Alternative parenteral formulations employing lipid vehicles for AmB delivery were developed in order to improve drug tolerability and optimize its clinical efficacy [79,95]. Three of such lipid-based formulations reached the market in the 1990s after approval by the United States Food and Drug Administration (FDA, Silver Spring, MD, USA) and the European Medicines Agency (EMA, Amsterdam, the Netherlands) [25,79], remaining commercially available in several countries:…”
Section: Commercial Amphotericin B Lipid Formulationsmentioning
confidence: 99%
“…AmB lipid formulations exhibit distinct pharmacokinetic profiles (Table 1) and are not interchangeable [95][96][97][98][99][100][101][102][103][104][105][106], having different dosing recommendations.…”
mentioning
confidence: 99%
“…Structurally, L‐AmB contains unilamellar vesicles composed of hydrogenated soy phosphatidylcholine and distearoyl phosphatidylglycerol, stabilized by cholesterol and combined with amphotericin B . Clinical studies have demonstrated higher plasma levels with L‐AmB when compared to conventional formulations of AmB with lesser incidence of nephrotoxicity . In a randomized, double‐blind, clinical trial comparing 2 doses of L‐AmB (3 and 6 mg/kg/d) and AmB (0.7 mg/kg/d), efficacy was similar between the three groups while toxicity was significantly lower in the L‐AmB groups.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Use of the Naranjo adverse drug reaction probability scale indicated a highly probable relationship between the ST‐elevated myocardial infarction and L‐AmB . The event occurred after administering L‐AmB twice (4), went away following removal of L‐AmB (1), had objective evidence from the ECG (1), had other causes ruled out (2), clean heart catheterization), and was less severe when the infusion rate was decreased (1) for a total score of 9 .…”
Section: What Is New and Conclusionmentioning
confidence: 99%